Stability Assessment of the Dam of a Tailings Pond Using Computer Modeling—Case Study: Coroiești, Romania - Florin Dumitru Popescu; Sorin Mihai Radu; Andrei Andras; Ildiko Brinas; Mihaela-Olga Marita; Mirela Ancuta Radu; Constantin Laurentiu Brinas (Applied Sciences, 2023)
Anthropogenic activities related to mining generate both progress and a vast amount of waste that is responsible for environmental degradation. The Jiu Valley is one of the areas of Romania where mining has affected large areas of land, used to build mines and tailings ponds. The former Coroiesti coal processing plant (CCPP) is such a location with a total area of 25 ha containing approximately 5.5 million tons of tailings. The assessment of the stability of tailings dams is extremely important from safety and environmental aspects. This study proposes a solution based on numerical methods for determining the stability of a section of the dam of a tailings pond. The model of tailings pond no. 1, compartment B, from the Coroieşti Coal Preparation was built using COMSOL Multiphysics. Two scenarios of stability analysis were conducted on a section of the tailings dam: the FOS was determined using the shear strength reduction (SSR) method for both the initial and the current state of this TP. This method is a modern alternative to the limit equilibrium method, and its implementation by COMSOL is new to our country, thus aligning this methodology with current worldwide trends and developments in the field. The results obtained proved to be in line with those calculated in the past with traditional analytical methods, proving that the safety criteria of the studied TP/TD are being met.